2004
DOI: 10.1063/1.1652015
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the hydrophobic hydration and interaction of simple solutes: An examination of five popular water models

Abstract: We examine five different popular rigid water models (SPC, SPCE, TIP3P, TIP4P and TIP5P) using molecular dynamics simulations in order to investigate the hydrophobic hydration and interaction of apolar Lennard-Jones solutes as a function of temperature in the range between 275 K and 375 K along the 0.1 MPa isobar. For all investigated models and state points we calculate the excess chemical potential for the noble gases and Methane employing the Widom particle insertion technique. All water models exhibit too … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
328
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 274 publications
(379 citation statements)
references
References 85 publications
49
328
2
Order By: Relevance
“…This finding may help to assess prior studies that used effective ranges of cm attraction as large as 6.5Å [31,32]. db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water. As such, db's are pertinent to the α-β transition in amyloidogenesis [26,27], which can be affected by pressure [27,[74][75][76].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding may help to assess prior studies that used effective ranges of cm attraction as large as 6.5Å [31,32]. db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water. As such, db's are pertinent to the α-β transition in amyloidogenesis [26,27], which can be affected by pressure [27,[74][75][76].…”
Section: Discussionmentioning
confidence: 96%
“…As such, db's are pertinent to the α-β transition in amyloidogenesis [26,27], which can be affected by pressure [27,[74][75][76]. Atomic PMF simulations indicated that temperature lowers both the cm and the db [34,37,38,42] whereas pressure raises them [77]. Inasmuch as a lower cm favors β (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water phase is represented by 1000 TIP5P water molecules [50]. The TIP5P model was chosen, since it represents the hydrophobic solvation behavior of water on the lowtemperature side probably most realistically among the simple point charge models [26]. Moreover, the temperature dependent strength of the hydrophobic interaction was found to be quite critically linked to the temperature dependence of waters expansivity [26].…”
Section: A MD Simulation Detailsmentioning
confidence: 99%
“…The TIP5P model was chosen, since it represents the hydrophobic solvation behavior of water on the lowtemperature side probably most realistically among the simple point charge models [26]. Moreover, the temperature dependent strength of the hydrophobic interaction was found to be quite critically linked to the temperature dependence of waters expansivity [26]. The simulations discussed here were carried over a broad temperature range at pressures of 1 bar, 3000 bar, and 4500 bar.…”
Section: A MD Simulation Detailsmentioning
confidence: 99%